2014
DOI: 10.1016/j.quaint.2013.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Response of vegetation in central Japan to precession during the last 147,000 years: A lignin record from Lake Biwa core BIW08-B

Abstract: 19To understand the responses of terrestrial vegetation in central Japan to global 20 climate changes, we generated a record of lignin composition from core BIW08-B in 21 Lake Biwa, central Japan, during the last 147,000 years by TMAH-pyrolysis-GC/MS. 22Lignin abundance was intermittently elevated and associated with a high ratio of 23 cinnamyl (C) to vanillyl (V) phenols (C/V ratio) of lignin, suggesting episodic inflows 24 1 of herbaceous plant-derived organic matter into Lake Biwa. The largest inflow occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…6). Ohira et al (2013) reported a spike of abundant lignin at the same layer in core BIW08-B. Because of low-CBT-based pH (3.3 to 8.0 with an average of 5.0; Ajioka et al, 2014) due to high CBT in the soils, the high CBT (low estimated pH) at 13 ka associated with high lignin abundance likely reflected the soil GDGT contribution.…”
Section: Changes In Lake Water Ph During the Last 280 Kymentioning
confidence: 97%
See 1 more Smart Citation
“…6). Ohira et al (2013) reported a spike of abundant lignin at the same layer in core BIW08-B. Because of low-CBT-based pH (3.3 to 8.0 with an average of 5.0; Ajioka et al, 2014) due to high CBT in the soils, the high CBT (low estimated pH) at 13 ka associated with high lignin abundance likely reflected the soil GDGT contribution.…”
Section: Changes In Lake Water Ph During the Last 280 Kymentioning
confidence: 97%
“…Proxies applicable to lake sediments include pollen and diatom fossils, δD of long-chain n-alkanes, lignin, biogenic opal, and pigments, among others. In Lake Biwa, sediment cores have been investigated using pollen fossils (Miyoshi et al, 1999;Nakagawa et al, 2008), lignin T. Ajioka et al: MBT /CBT indices (Ishiwatari and Uzaki, 1987;Ishiwatari et al, 2009;Ohira et al, 2013), diatom frustules (Kuwae et al, 2004), biogenic opal (Xiao et al, 1997), pigments (Ishiwatari et al, 2009), and δD of long-chain n-alkanes (Seki et al, 2012). Although palaeoclimate information is available from these proxy records, more records generated by other new proxies are necessary to better understand the response of the East Asian monsoon to orbital forcing.…”
Section: Introductionmentioning
confidence: 99%
“…6). Ohira et al (2013) reported a spike of abundant lignin at the same layer in core BIW08-B. Because of low-CBT-based pH (3.3 to 8.0 with an average of 5.0; Ajioka et al, 2014) due to high CBT in the soils, the high CBT (low estimated pH) at 13 ka associated with high lignin abundance likely reflected the soil GDGT contribution.…”
Section: Changes In Lake Water Ph During the Last 280 Kymentioning
confidence: 99%
“…Proxies applicable to lake sediments include pollen and diatom fossils, δD of long-chain n-alkanes, lignin, biogenic opal, and pigments, among others. In Lake Biwa, sediment cores have been investigated using pollen fossils (Miyoshi et al, 1999;Nakagawa et al, 2008), lignin (Ishiwatari and Uzaki, 1987;Ishiwatari et al, 2009;Ohira et al, 2013), diatom frustules (Kuwae et al, 2004), biogenic opal (Xiao et al, 1997), pigments (Ishiwatari et al, 2009), and δD of long-chain n-alkanes (Seki et al, 2012). Although palaeoclimate information is available from these proxy records, more records generated by other new proxies are necessary to better understand the response of the East Asian monsoon to orbital forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Tp values refer to Kanauchi et al (2007). Figure 11 shows the S/V ratios in core TKN-2004 and other two cores, i.e., core BIW08-B from Lake Biwa in central Japan (Ohira et al, 2014) and core MD01-2421 off central Japan in the northwestern Pacific . All of these records showed good agreement, except in the MIS 6 to MIS 5d in MD01-2421 (Fig.…”
Section: Changes In the Contributions Of Gymnosperms And Angiospermsmentioning
confidence: 99%